A Semiotic exploration of Humour in South African fast-food advertisements as a strategy for Brand Likeability - Gulubela, Sbahle (The IIE, 2022)
Recently, more and more we have seen brands integrate humour as a strategy in advertising. Despite this growth however, humour is not used as frequently, or is often used in isolation as brands tend struggle to cater to large audiences. Humour can be tricky and often seem impossible without offending anyone, especially in recent times. So other than being seen as full proof method to getting your brand cancelled, how else could humour prove to be beneficial for brands? The following study analyses this very question by going back to the basics of advertising through the AIDA model and critically analysing the advertisement content itself. This research suggests that perhaps other components could be the key to successful humour advertising. Thus, taking the route of a semiotic exploration of humour in South African fast-food advertisements as a strategy in brand likeability. This research shows potential in this line of thinking with other components such as integration of personal experiences and repeated communication and exposure from brands, with a holistic view of the consumer experience. With the different components taken into consideration and integrated, and the factors influencing brand likeability addressed, fast food brands could manage to provide commentary and meals to their audience and increase their chances of brand likeability.
Keywords: Humour; Brand love; Advertising; Restaurants